No meio do caminho tinha uma pedra porosa: a metaficção da modernidade à Pós-modernidade - Valério, Alessandra Cristina (2016)
The research presented here is intended to address the literary phenomenon of metafiction and its performance, in particular, from the set of aesthetic and political principles that are conventionally designated by postmodernism, which is assigned the crucial condition descriptor of contemporary culture. From the survey of gaps and critical contradictions of other approaches to the same object, the proposal is to make our own conceptual construction of this fictional model, reminiscent of an important philosophical and literary tradition, articulated around the cognitive and aesthetic development of self-awareness and modern self-reflexivity (GUMBRECHT, 1998). Given that most of the studies of metafiction, until then, tends to exhaust the characteristics of a single object (author, work), exempting to establish wider connections between different self-conscious manifestations and self-reflexive and the epistemic lines in general, which are the forms of contemporary thought, this research seeks to build an interpretive system that integrates these discontinuities in a larger set of self-conscious cultural experiences. It is a connection line between modern literary self-consciousness (CERVANTES, STERNE, JOYCE) and postmodern metafiction, giving evidence of the main differences and connections between forms of activities of self-referential models in each context. To this end, the articulation of an expository approach to literary phenomenon that is not limited to the immanent aspect was necessary, much solidified position on some critical perspectives, but to consider the urgent need to understand literature as a complex communication system. As a result, the theoretical alternative that presented itself as the most productive in this case was the pragmatic approach of the literary act, announced some time ago by the Theory of Speech Acts of Austin and Searle, developed in the literary context by Derrida (1992), Culler (1999) and Maingueneau (1996).